COVID-19 and hospitality and tourism research: An integrative review. (September 2021) - Zopiatis, Anastasios; Pericleous, Katerina; Theofanous, Yiannis
Abstract: COVID-19 caused a shockwave in all facets of the contemporary tourism industry, triggering a surge in relevant research. Responding to the sheer magnitude of the event, and the plethora of research opportunities, scholars have been investigating the pandemic from an array of perspectives, at both a micro and macro level. With the aim of advancing the existing conceptual capital, this study uses a systematic integrative review to summarize, critique and synthesize the COVID-19-related studies published in hospitality and tourism journals; it identifies important gaps and highlights a future research agenda. We select 362 articles relevant to our analysis and conduct our research using VOSviewer visualization software. Findings, of particular interest and importance to scholars, illuminate thematic areas that may stimulate further research endeavors.